نموذج لبناء اختبار القراءة و الكتابة لأطفال ذوي صعوبات التعلم في المرحلة الابتدائية - دبراسو, فطيمة (جامعة الوادي University of Eloued, 2017)
الملخص: تعتبر صعوبات القراءة و الكتابة من بين أهم الصعوبات الأكاديمية التي يعاني منها الأطفال في المرحلة الابتدائية و التي تؤثر في بقية المواد الدراسية الأخرى، لذا يجب الكشف عنها و معالجتها بشكل مبكر و إلا يمكن أن تستمر لمراحل لاحقة. و لتشخيص هذه الصعوبات يحتاج الأخصائي النفسي إلى اختبارات في القراءة و الكتابة للكشف عن أهم مؤشراتها التي تتمثل في الحذف، القلب، الخلط، التكرار.....إلخ. لذا سوف نحاول في هذه الورقة توضيح أهم الخطوات لبناء اختبار في القراءة والكتابة لأطفال ذوي صعوبات التعلم و كيفية تحليله كميا و كيفيا من خلال دراسة الحالة. The difficulties of reading and writing encountered by the learners at the primary school which affect the rest of the other subjects are considered as the major hindrance for teachers. Because, this problem may last for all the learning process and affect all the other skills if not revealed and treated on time. In order to diagnose these difficulties, specialists in psychology need to proceed with tests that may reveal the indicators such as deletion, turning, confusion, repetition…. And thus try to find out remedial work. In this attempt, we shall try to clarify the most important steps for building a test for children with learning disabilities in the reading and the writing skills and how to analyze the results quantitatively as well as qualitatively for the purpose to find out a remedial treatment to get rid of these problems
دراسة حالة
مقال
Keywords: صعوبات التعلم؛ اختبار القراءة و الكتابة؛ التلميذ؛ دراسة حالة; learning disabilities; test for reading and writing; case study.